As residências com quatro pilares na arquitetura paulista 1958-2011 - Silva, Maíra Baltrusch Martins (2019)
This research addresses the primordial theme of architecture, that is, the home built by the human being, housing. The study is carried out based on a set of homes in São Paulo whose peculiarity is revealed in the amount of structure support, in this case only four. The phenomenon occurred in the history of São Paulo architecture in standardized se-ries, later called as Brutalism. By the records of published projects, the proposal was introduced by Joaquim Guedes with the project of the house Cunha Lima (1958). It was consecrated through the production of Vilanova Artigas and Paulo Mendes Rocha. This architectural concept was so deeply rooted in the idealism of São Paulo that it is repeated to the present day. This research compiled and cataloged the residences built from 1958 to 2011, the focus was restricted to the architects of São Paulo, understanding as such those whoha-ve or had their office based in São Paulo, regardless of their origin. In addition to the collection of data of residences the work aims to explain the reasons for the adoption of such concept.